Screening the low molecular weight fraction of human serum using ATR‐IR spectroscopy. Issue 10 (10th August 2016) - Bonnier, Franck; Brachet, Guillaume; Duong, Romain; Sojinrin, Tobiloba; Respaud, Renaud; Aubrey, Nicolas; Baker, Matthew J.; Byrne, Hugh J.; Chourpa, Igor
Abstract : Vibrational spectroscopic techniques can detect small variations in molecular content, linked with disease, showing promise for screening and early diagnosis. Biological fluids, particularly blood serum, are potentially valuable for diagnosis purposes. The so‐called Low Molecular Weight Fraction (LMWF) contains the associated peptidome and metabolome and has been identified as potentially the most relevant molecular population for disease‐associated biomarker research. Although vibrational spectroscopy can deliver a specific chemical fingerprint of the samples, the High Molecular Weight Fraction (HMWF), composed of the most abundant serum proteins, strongly dominates the response and ultimately makes the detection of minor spectral variations a challenging task. Spectroscopic detection of potential serum biomarkers present at relatively low concentrations can be improved using pre‐analytical depletion of the HMWF. In the present study, human serum fractionation by centrifugal filtration was used prior to analysis by Attenuated Total Reflection infrared spectroscopy. Using a model sample based on glycine spiked serum, it is demonstrated that the screening of the LMWF can be applied to quantify blinded concentrations up to 50 times lower. Moreover, the approach is easily transferable to different bodily fluids which would support the development of more efficient and suitable clinical protocols exploring vibrational spectroscopy based ex‐vivo diagnostic tools.Revealing serum LMWF for spectral serological diagnostic applications. Abstract : The Low Molecular Weight Fraction (LMWF) of serum holds great potential for diagnostics and health monitoring. The low concentrations of peptides and metabolites compared to highly abundant proteins remain a challenging obstacle to overcome. In order to collect specific chemical fingerprint from small serum biomolecules using vibrational spectroscopy techniques, High Molecular Weight (HMW) proteins depletion is required. Physical separation by mean of ultrafiltration offers a new dimension in serological diagnostic and further support the potential of Infrared and Raman spectroscopy as clinical tools.